Kesiapan Peserta Didik dalam Menghadapi Ujian Nasional di SMP Negeri 31 Padang - Pinalia, Roza - (Bimbingan dan Konseling, 2014)
This researcd was based on motivated by the level of understanding of learner about the readiness of student to face national exam. Researcd based on observation at SMP Negeri 31 Field on 2 December 2013 that there are still student who are not ready to face the un pre exam due to lack of understanding regarding the readiness of student in the exam are many problem experienced by learner such as the existence of a sleepy learner when facing exam, any participant who requested permission to leave to buy food and drink because of thirst and weak, the presence of students who are sick when an exam, any participant to borrow her equipment time for exam, any learner who lack concentration in the exam, and the presence of incomplete learner carryng equipment in the exam. The objective of this study ave: 1) The physical readiness of students in national exams. 2) Psychological readiness of learnes in national exam. This researcd was descriptive qualitative research sampling was done by using proportional stratified random sampling. This study took a sample of studentâs who serve as the responden who are 71. Additional responden were supervising teacher and subject teacher. Instrument used in this study was a questionnaire. While the use of data analysis technique for the percentage. The researcd results a led that: 1) The physical readiness of learner in the national exam are the criteria prepaced 56,34% of the respondent. 2) Phychological readiness of studentâs in national exam are the criteria of 61,98% of respondent.